Superhydrophobic leached carbon Black/Poly(vinyl) alcohol aerogel for selective removal of oils and organic compounds from water. (January 2022) - Tai, Ming Hang; Mohan, Babu Cadiam; Yao, Zhiyi; Wang, Chi-Hwa
Abstract: The remediation of oil spills and treatment of oily wastewater remains challenging to cope with nowadays. This has caused a surge in demand on adsorbent materials with multi-functionalities to effectively separate oils and nonpolar solvents from water. A superhydrophobic composite aerogel prepared from industrial waste-derived leached carbon black waste (LCBW) and polyvinyl alcohol (PVA) was developed in this work via conventional freeze-casting followed by surface coating. The composite aerogel was ultralight and porous with porosity >85% and tunable density ranging between 0.015 and 0.065 g/cm 3 . It was found that the embedded LCBW in the PVA network is crucial to impart superhydrophobicity and superoleophilicity to the aerogel as it enhances the surface roughness. Wettability test showed that composite aerogel prepared from 0.5 wt% PVA at PVA/LCBW ratio of 1 exhibited the highest water contact angle (156.7 ± 2.9°). LCBW also improved the thermal stability of the composite aerogel. With its superior selectivity, PVA/LCBW aerogel was used as selective adsorbent for a variety of oils and organic solvents. The adsorption test showed that the composite aerogel exhibited an adsorption capacity up to 35 times its original weight and could be reused repeatedly and easily recovered through a simple drying method. Graphical abstract: Image 1 Highlights: A highly porous PVA/LCBW aerogel is prepared by conventional freeze-casting. Superhydrophobicity of aerogel is resulted from carbon black waste. Carbon black waste reduces aerogel's shrinkage and improves thermal stability. Aerogel exhibits sorption capacity of ~30 g/g for oils and organic solvents.